Programas de cumplimiento: un modelo para armar - Bustinza Siu, Marco (2018)
The purpose of this contribution is to identify the foundations of Compliance Programs, both in public policy and in criminal law, and to denounce the successes and failures of a criminal policy that is in itself adequate and still perfectible.